(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In India till 1991 there was only one television channel–Doordarshan, the public service broadcaster. With the opening up of the Indianeconomy in early 1990s enabled the entry of private broadcasters in India. Thenumber of television channels has proliferated manifold. By 2005 India had morethan 200 digital channels. The number of television channels has grown fromaround 600 in 2010 to 800 in 2012.This includes more than 400 news and currentaffairs channel. Technological changes have caused intense competition in newsand general entertainment channels, as a result of which there is growth inregional and niche channels. The growth of cable and satellite television anddirect to home television services has continued to drive television as themost preferred medium among advertisers. Broadcasters are also tapping into online and mobilemedia to increase their revenue. This paper seeks to study the impact ofprivatisation on media policy of the Government of India and how it has evolvedvarious institutional mechanisms to deal with the growth of television as themedium to study the effect of privatisation and convergence on mediaregulations as television is the most powerful medium. The visual imagestransmitted by television reach large section of the Indian populationirrespective of linguistic and cultural differences. The paper initiateswith mankind, globalization and the contemporary mass media role played throughmultiple media approach at the dawn of third millennium and the need to addressthe challenge of technological pluralism. Then the concepts and influences ofnew media technologies related communications through the internet, cellphones, multimedia, gaming and animation, portals, etc, are enunciated.Perspectives of Culture, new media culture and its impact on society are dealtwith. Later, the importance of studies on culture and relevance of technologyin cultural studies are explained.